Elderberry Leaves with Antioxidant and Anti-Inflammatory Properties as a Valuable Plant Material for Wound Healing - Elżbieta Studzińska-Sroka; Magdalena Paczkowska-Walendowska; Zuzanna Woźna; Tomasz Plech; Piotr Szulc; Judyta Cielecka-Piontek (MDPI AG, 2024)
Sambuci folium (elderberry leaves) have been used in traditional medicine, mainly externally, to treat skin diseases and wounds. Therefore, the aim of this study was to screen the biological activity of elderberry leaves (antioxidant potential and possibility of inhibition of tyrosinase and hyaluronidase enzymes) combined with phytochemical analysis. For this purpose, a phytochemical analysis was carried out. Elderberry leaves of 12 varieties ("Sampo", "Obelisk", "Dwubarwny", "Haschberg", "Haschberg 1", "Koralowy", "Sambo", "Black Beauty", "Black Tower", "Golden hybrid", "Samyl", "Samyl 1") in two growth stages. The compounds from the selected groups, phenolic acids (chlorogenic acid) and flavonols (quercetin), were chromatographically determined in hydroalcoholic leaf extracts. All tested elderberry leaf extracts showed antioxidant effects, but the most promising potential: very high compounds content (TPC = 61.85 mg GAE/g), antioxidant (e.g., DPPH IC50 = 1.88 mg/mL; CUPRAC IC0.5 = 0.63 mg/mL) and optimal anti-inflammatory (inhibition of hyaluronidase activity 41.28%) activities were indicated for older leaves of the "Sampo" variety. Additionally, the extract obtained from "Sampo" and "Golden hybrid" variety facilitated the treatment of wounds in the scratch test. In summary, the best multidirectional pro-health effect in treating skin inflammation was specified for "Sampo" leaves II extract (leaves during the flowering period); however, wound treatment was noted as rich in chlorogenic acid younger leaf extracts of the "Golden hybrid" variety.